2023
DOI: 10.1039/d3qm00657c
|View full text |Cite
|
Sign up to set email alerts
|

Nitrides: a promising class of nonlinear optical material candidates

Xin Zhao,
Chensheng Lin,
Haotian Tian
et al.

Abstract: Nonlinear optical (NLO) materials play a crucial role in all-solid-state lasers, as their frequency conversion effects enable the expansion of the limited and fixed frequency outputs of lasers to encompass...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 94 publications
2
5
0
Order By: Relevance
“…The linear and NLO properties of GaN and Si 3 N 4 , which are benchmark materials in the nitride system, have been calculated with high accuracy. These calculations confirm the accuracy of theoretical studies in predicting novel materials. , For computational details, see the Supporting Information.…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…The linear and NLO properties of GaN and Si 3 N 4 , which are benchmark materials in the nitride system, have been calculated with high accuracy. These calculations confirm the accuracy of theoretical studies in predicting novel materials. , For computational details, see the Supporting Information.…”
Section: Methodssupporting
confidence: 75%
“…This effect is stronger than that of α-Si 3 N 4 (∼1.07 pm/V) and AlN (∼1.20 pm/V), although it is smaller than that of 4H-SiC (∼6.63 pm/V) and GaN (∼4.44 pm/V). However, its Δ n is much larger than 0.04, resulting in a dominant effective SHG effect for its phase matching . It is noteworthy that the Δ n of γ-P 3 N 5 is the largest compared to these structures, slightly larger than 0.11 of β-Ga 2 O 3 (owing to the distorted tetrahedra [GaO 4 ] and pyramid [GaO 3 ] with large structural anisotropy).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The information in this study is primarily obtained from first-principles calculations found in the existing literature. Notably, the calculated results on the linear and NLO properties for the benchmark materials GaN and Si 3 N 4 in the nitride system exhibit remarkable accuracy [26,30], supporting the reasonableness and dependability of the theoretical studies for use clarifying structure-property correlations and anticipating new materials. In this paper, to enhance the lucidity of the structure-property evolutions, we include additional data while maintaining computational parameters' consistency.…”
Section: Methodssupporting
confidence: 53%
“…This mainly includes the CN-based NLO system [24], PN-based NLO system [25], and SiN-based NLO system [26], which has a larger bandgap E g than GaN (~3.4 eV), as well as other nitrides such as Zn 2 NCl [27] and NaSnN [28], the latter having a smaller bandgap E g than GaN. These NLO nitrides show a variety of anionic group structures and structure-property relationships [29][30][31][32][33][34]. Encouragingly, the output wavelengths of their phase-matching SHG can span the UV spectrum and even extend into the deep-UV bands.…”
Section: Introductionmentioning
confidence: 99%